Improving the Motivation and Learning Outcomes of Learners Through Scientific Approach in SDN Citepus 01 - Sariyah, Sariyah (Universitas Sebelas Maret, 2020)
The purpose of this research is to increase the motivation and learning outcomes of learners in the material PPKn pancasila first practice sila using scientific shortata can improve the motivation and learning outcomes of learners.In the first cycle showed learning motivation (60%) and learning outcomes (55%). In Cycle II, it is able to increase learning motivation (75%)and learning outcomes (80%). In SiklusIII is able to increase learning motivation (95%) and learning outcomes (95%). In The First Cycle, Learning completeness reached 55% with an average value of 70.01. cycle II reaches 80% with an average value of 76.15.In Cycle III it reaches 95% with an average value of 96.00.